Experiential Insights from Managing Joint Ventures in Indonesia : Reflection on Past Lessons and Future Challenges - Pawitra, Teddy (UI Scholars Hub, 2009)
Joint ventures as one of the many form of strategic alliance are now ubiquitous phenomena in most Asian countries such as Indonesia and others. The trend to establish joint ventures with foreign firms has been growing in popularity since the onset of 1980s. In 2007, the value of realized foreign direct investment in Indonesia had reached USD 9,076.6 million which represented 842 projects (Investment Coordinating Board, Oct. 2007). However, particular data regarding the magnitude of investment in joint ventures are not available because foreign direct investments are not further specified into joint ventures and wholly owned subsidiaries. The development of joint ventures is more discernible if we turn to the international business arena. Over the past few years more than 5000 joint ventures have been established and the largest world 100 joint ventures represent more than USB 350 billion in combined annual revenues (Bomford, Erns and Fubini, 2004).